Panaik Money of Bugis’ Customary Marriage in the Perspective of Islamic Law and Positive Law in Indonesia - Shofiatul Jannah; Mufidah CH; Suwandi Suwandi (Journal of Transcendental Law, 2021)
This article discusses the giving of panaik money to the Bugis marriage customs outside of the dowry obligation. This culture has long been carried out at traditional Bugis weddings. The custom of giving panaik money has become a topic of discussion among academics because it is not included in the pillars and conditions of marriage in Islam or positive law. This is a custom that is sometimes considered burdensome to the prospective groom to cause the marriage to be annulled. This research is library research with a normative approach. It uses a qualitative method, namely, observing and reviewing the obligation to give money for traditional Bugis marriages outside of the dowry. The results of the panaik money research in the study of Islamic law do not conflict with the terms and pillars of marriage. As for the positive legal view, in this case, Law Number 1 of 1974 concerning Marriage concludes that panaik money does not conflict with formal or material requirements, namely in articles 6 to 10, which explain the existence of cultural fusion between customary law and Islamic law in Indonesia which has been recognized. As part of the source of material law in Indonesia. As for the cultural pattern of Bugis ethnic marriage, panaik money is a form of respect and appreciation from the male family to the female family.Panaik Money, Islamic Law, Positive Law, Cultural Customs